2023
DOI: 10.3390/ijms24021763
|View full text |Cite
|
Sign up to set email alerts
|

Can Zinc Supplementation Attenuate High Fat Diet-Induced Non-Alcoholic Fatty Liver Disease?

Abstract: The pathogenesis of non-alcoholic fatty liver disease (NAFLD), the most prevalent chronic liver disease, is associated with zinc deficiency. Previous studies show zinc supplementation improves steatosis and glucose metabolism, but its therapeutic effects in patients with established NAFLD remain unclear. We developed an in vivo model to characterize the effects of zinc supplementation on high-fat diet (HFD) induced NAFLD and hypothesized that the established NAFLD would be attenuated by zinc supplementation. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
1
1
Order By: Relevance
“…Serum zinc concentrations are reduced in patients with non-alcoholic fatty liver disease [47] and there may be an association of lower serum zinc and greater severity of non-alcoholic fatty liver disease in humans [48,49]. However, in the present study, neither marginal Zn deficiency nor Zn supplementation altered the relative liver weight or the hepatic triglyceride levels of ZDF rats, and similarly others have reported that zinc supplementation did not alter the hepatic steatosis score of mice fed high-fat diets [50]. Dyslipidemia, especially low HDL-cholesterol and elevated triglycerides, is a common feature of type 2 diabetes in humans [2].…”
Section: Discussioncontrasting
confidence: 60%
“…Serum zinc concentrations are reduced in patients with non-alcoholic fatty liver disease [47] and there may be an association of lower serum zinc and greater severity of non-alcoholic fatty liver disease in humans [48,49]. However, in the present study, neither marginal Zn deficiency nor Zn supplementation altered the relative liver weight or the hepatic triglyceride levels of ZDF rats, and similarly others have reported that zinc supplementation did not alter the hepatic steatosis score of mice fed high-fat diets [50]. Dyslipidemia, especially low HDL-cholesterol and elevated triglycerides, is a common feature of type 2 diabetes in humans [2].…”
Section: Discussioncontrasting
confidence: 60%
“…One of the important mechanisms by which zinc deficiency leads to disturbed protein metabolism in patients with chronic liver disease is diminished ammonia metabolism, which may potentially induce or exacerbate endoplasmic reticulum stress and apoptosis, thereby triggering MAFLD [237,241]. Zinc supplementation attenuates high-fat diet-induced hepatic steatosis and liver injury, which is achieved partly by improving glucose-lipid metabolism disorders, but zinc intervention cannot alleviate MAFLD caused by a high-fat diet [242,243]. Nonetheless, a randomized clinical trial observed elevated zinc levels and reduced hepatic enzyme levels in serum after zinc supplementation in patients with overweight/obesity and MAFLD [244].…”
Section: Zinc Metabolism and Mafldmentioning
confidence: 99%